A corresponding state equation for compressed liquid isochoric heat capacity of pure and mixture refrigerants. (April 2021) - Sheng, Bowen; Zhao, Yanxing; Dong, Xueqiang; Yan, Han; Zhong, Quan; Wang, Jingzhou; Shen, Jun; Gong, Maoqiong
Highlights: A simple corresponding state equation for compressed liquid isochoric heat capacity of pure and mixture refrigerants was developed. The present equation contains two constant coefficients and only depends on reduced temperature. The equation is in good agreement with compressed liquid cv experimental data of pure and mixture refrigerants. The equation can be used to predict cv of pure and mixture refrigerants in compressed liquid states. Abstract: This work proposed a simple corresponding state equation depending on reduced temperature to predict compressed liquid isochoric heat capacity ( cv ) for HCs, HCFCs, HFCs and HFOs pure and mixtures at 0.3 < T r < 1 and 0.5 < p r < 10. The generalized constant coefficients A and B were determined by regression of 1738 experimental cv data for 16 refrigerants including HCs, HFCs, HCFCs and HFOs in compressed liquid states ( ρ > 2 ρc ). With known critical parameters, acentric factor and ideal gas isochoric heat capacity, the developed equation can represent the compressed liquid cv well with the average absolute relative deviation (AARD) of 1.82%. Compared with the generalized equation of Zhong et al. (2019a) and the special multiproperty equations in REFPROP 10.0 software, the proposed equation is slightly poor in accuracy, but simpler in form and requires fewer parameters. In addition, liquid cv data of 13 pure and 9 mixtures were used to verify the prediction performance of the developed equation and the applicability to the mixtures. The equation in this work is in good agreement with the experiment cv data of 9 pure and 9 mixtures including HCs, HFCs, HCFCs and HFOs, but the large deviation for 4 substances (N2, CO2, H2 O and CH3 OH).